Antifungal Packaging Film to Maintain Quality and Control Postharvest Diseases in Strawberries - Valentina Trinetta; Austin McDaniel; Konstantinos G. Batziakas; Umut Yucel; Londa Nwadike; Eleni Pliakoni (MDPI AG, 2020)
Strawberries are a highly perishable crop with postharvest losses than reach up to 40%. Cost-effective and sustainable technologies in the form of active packing films can provide a solution. Antimicrobial packaging films were produced from pullulan polymer and Solid Lipid Nanoparticles (SLN) containing 1% w/w cinnamaldehyde. Strawberries were stored at 3 °C for 10 days and 12 °C for 6 days. Microbial and physical quality parameters were evaluated during storage. A reduction of approximately 2 Log CFU/g in yeast and mold population was observed for treated strawberries stored at 3 °C as compared to the control (p < 0.05). Yeast and molds counts were significantly lower on day 2 and 4 at 12 °C for treated samples. Strawberries packaged with the active films demonstrated lower respiration rates and the retention of bright red color at both storage temperatures. Active pullulan films were effective in maintaining the desired strawberry quality and reducing fungal decay during refrigerated storage.